Students’ Motivation in Listening English Songs Comprehension at SMP Muhammadiyah 5 Tulangan - Jazilah, Rania Ni’matul; Mandarani, Vidya (Pubmedia Jurnal Pendidikan Bahasa Inggris, 2024)
Listening is one of the language components that must be learned by students because learning to listen is very beneficial for students to hone their sensitivity to hear English vocabulary. This study focuses on students' motivation in listening to English songs. The purpose of this study was to determine students' motivation and understanding in listening to English songs. This research employs a quantitative descriptive research design. The subjects of this research were 30 students in grade VIII SMP Muhammadiyah 5 Tulangan for the 2022/2023 academic year. Data collection techniques used in this study were observation, interviews and questionnaires. Observations were made prior to the study to find out the teaching methods that had been carried out during listening lessons. Interviews were conducted with English teachers to find out whether they had ever practiced listening song lessons. Questionnaires were used to determine the level of understanding and motivation of students. The measurement scale in this study uses a likert scale. The results of this study were analyzed descriptively to determine students' motivation and comprehension in listening to English songs. The benefit of this research is to increase the motivation and comprehension of VIII grade students in understanding English songs. The findings revealed that students' motivation to listen to English songs was very high, with an average of 86%. Meanwhile, the indicator of understanding in listening to English songs obtained an average student score of 81.11%.